High-performance sodium-ion hybrid capacitors based on an interlayer-expanded MoS2/rGO composite: surpassing the performance of lithium-ion capacitors in a uniform system. (August 2018) - Zhan, Changzhen; Liu, Wei; Hu, Mingxiang; Liang, Qinghua; Yu, Xiaoliang; Shen, Yang; Lv, Ruitao; Kang, Feiyu; Huang, Zheng-Hong
Abstract Hybrid supercapacitors (HSCs) are novel, promising devices having features of both batteries and supercapacitors. Herein, we report HSCs (Li-HSC and Na-HSC in a uniform system) based on an interlayer-expanded MoS2 /rGO composite that show ultrahigh energy density and power density as well as superior cycle stability. The 3D network-structured interlayer-expanded MoS2 /rGO nanocomposite (3D-IEMoS2 @G) was synthesized and employed as the anode. Because the 3D architecture of the graphene skeleton frame delivered sufficient charges and the highly interlayer-expanded MoS2 achieved fast ion diffusion, the as-prepared composite exhibited excellent performance as the anode material for both LIBs and SIBs (1600 mAh g− 1 at 100 mA g−1 for the LIB; 580 mAh g−1 at 100 mAh g−1 and 320 mAh g−1 at a high current density of 10 A g−1 ). When paired with nitrogen-doped hierarchically porous 3D graphene (N-3DG), the obtained Na-HSC surpassed Li-HSC in a uniform system, showing an excellent performance of 140 Wh kg− 1 at 630 W kg− 1, 43 Wh kg− 1 at an ultrahigh power density of 103 kW kg− 1 (charge finished within 1.5 s) and no distinct capacity attenuation after over 10000 cycles. Thus, a quantitative kinetic analysis was performed to understand the synergistic effect of the two electrodes and the resulting effect of ions in the hybrid supercapacitors and to further pave a general path for fabricating high-performance HSCs. Energy storage: Getting the best of both worlds An energy storage device that combines the advantages of batteries and capacitors has been developed by researchers in China. Batteries store energy electrochemically as charged ions, while supercapacitors store electrical charge electrostatically on a surface. This gives supercapacitors the advantage that they can be charged very quickly, and charged and discharged many times, but they can't store as much energy as a battery of the same weight. Zheng-Hong Huang from Tsinghua University in Beijing and co-workers created a hybrid device that exhibited both ultra-high energy and power density along with excellent cycle stability. Their structure had an anode made from a composite of interlayer-expanded molybdenum disulfide and graphene oxide. The three-dimensional graphene skeleton supported the electrical charge, while the interlayer-expanded molybdenum disulfide enabled rapid diffusion of ions and provided sufficient energy storage sites. Sodium ion hybrid capacitors is fabricated by interlayer-expanded MoS2 /rGO composite and it shows greater performance than lithium ion capacitor.